2021
DOI: 10.1021/acsaem.1c02247
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Storage Performance and Investigation of Electrochemical Mechanism of Cobalt Vanadate Nanowires Assembled by Nanosheets

Abstract: Cobalt vanadate (Co 3 V 2 O 8 , CVO) nanowires assembled by nanosheets are successfully synthesized using a two-step hydrothermal method. Annealing temperatures can alter the specific surface area of the CVO samples. The physicochemical and electrochemical properties of these CVO samples are systematically characterized and compared. Impressively, the as-prepared CVO exhibits a higher reversible specific capacity and better rate performance than other annealed CVO electrodes, including a specific capacity of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The peak placed at 265 cm −1 is associated with the B 2g bending mode of the VO 4 3− group. Additionally, the Raman shifts at 325 and 387 cm −1 are ascribed to the E g bending mode, and the peak found at 448 cm −1 is connected with the B 1g bending mode 34,35. The variation trend of low peak intensity corresponds to the change of the A 1g symmetric stretching mode in all samples.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The peak placed at 265 cm −1 is associated with the B 2g bending mode of the VO 4 3− group. Additionally, the Raman shifts at 325 and 387 cm −1 are ascribed to the E g bending mode, and the peak found at 448 cm −1 is connected with the B 1g bending mode 34,35. The variation trend of low peak intensity corresponds to the change of the A 1g symmetric stretching mode in all samples.…”
mentioning
confidence: 75%
“…Additionally, the Raman shifts at 325 and 387 cm −1 are ascribed to the E g bending mode, and the peak found at 448 cm −1 is connected with the B 1g bending mode. 34,35 The variation trend of low peak intensity corresponds to the change of the A 1g symmetric stretching mode in all samples. Overall, the introduction of ILs interacts with metal salts and weakens the interaction energy between Co−V−O, which may be conducive to the formation of surface structural defects.…”
Section: Structural Characteristics Of Cvo Precursors and Catalystsmentioning
confidence: 88%
“…8,9 Among them, vanadium oxides have attracted extensive interest as potential battery materials because of the multiple valence states of vanadium (V 5+ , V 4+ , V 3+ , and V 2+ ) and the rich structural chemistry, which enable versatile redox-dependent properties. 10,11 Thus, vanadium oxides can deliver remarkable theoretical capacities, which are much higher than that of the commercialized graphite anode (372 mA h g −1 ). 1,[12][13][14] However, their viability in practi-cal batteries is hampered by their limitations of poor conductivity, inferior ion kinetics, and severe volume changes upon cycling.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Nevertheless, similar to other transition metal oxides, manganese vanadate suffers from some disadvantages such as poor conductivity for electron transfer and ion diffusion, and severe volume changes during the charging and discharging process, leading to crushing of the electrode material and thus a suboptimal rate performance and cycling stability. To address these issues, many strategies have been used to overcome these drawbacks, such as nanohybrids, 6,10,12,31 surface-coating, 5,11,32 interfacial engineering, 33 and element-doping. 34 Thereinto, the doping strategy is an effective method to improve the electrical conductivity of transition metal oxides, and can introduce oxygen vacancies, cations, and anions to modulate the energy band structure, thus improving their electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the wide band gap of T-Nb 2 O 5 (∼4 eV) indicates a poor electronic conductivity (3.4 × 10 –6 S cm –1 ) and shackles the charge-transport characteristics, which probably results in an inferior rate capacity and low reduction reaction degree during the discharging process. , Different methods have been proposed to address these issues. One of the most universal strategies has been to design delicate nanostructures integrated with carbonaceous materials, which aimed to decrease the diffusion distance of Li + and enhance the electronic conductivity of the electrode simultaneously. , Although the application of this technology can achieve the desirable high rate performance, there is also perceptible degradation during the cycling process duo to the overexposed grain boundaries of the nanostructure in the electrolyte, such as the irreversible decomposition of the electrolyte, morphological changes, and a high initial capacity loss. The delicately designed micrometer-scaled materials can also exhibit desirable performance, and Grey et al demonstrated that, with the appropriate host lattice, none of the usual size, structure, or porosity criteria are required to achieve a practical high-rate battery electrode .…”
Section: Introductionmentioning
confidence: 99%